The addition of chemotherapy to adjuvant radiation is associated with inferior survival outcomes in intermediate‐risk HPV‐negative HNSCC. (2nd May 2021) - Tasoulas, Jason; Lenze, Nicholas R.; Farquhar, Douglas; P. Schrank, Travis; Shen, Colette; Shazib, M. Ali; Singer, Bart; Patel, Shetal; Grilley Olson, Juneko E.; Hayes, David N.; Gulley, Margaret L.; Chera, Bhishamjit S.; et al.
Abstract: Background: Only high‐risk tumors with extranodal extension (ENE) and/or positive surgical margins (PSM) benefit from adjuvant therapy (AT) with concurrent chemoradiation (CRT) compared to radiation therapy (RT) in locally advanced head and neck squamous cell carcinoma (HNSCC). Optimal treatment for intermediate‐risk tumors remains controversial. We categorized patients based on their surgical pathologic risk factors and described AT treatment patterns and associated survival outcomes. Methods: Patients were identified from CHANCE, a population‐based study, and risk was classified based on surgical pathology review. High‐risk patients (n = 204) required ENE and/or PSM. Intermediate‐risk (n = 186) patients had pathological T3/T4 disease, perineural invasion (PNI), lymphovascular invasion (LVI), or positive lymph nodes without ENE. Low‐risk patients (n = 226) had none of these features. Results: We identified 616 HPV‐negative HNSCC patients who received primary surgical resection with neck dissection. High‐risk patients receiving AT had favorable OS (HR 0.50, p  = 0.013) which was significantly improved with the addition of chemotherapy compared to RT alone (HR 0.47, p  = 0.021). When stratified by node status, the survival benefit of AT in high‐risk patients persisted only among those who were node‐positive (HR: 0.17, p  < 0.0005). On the contrary, intermediate‐risk patients did not benefit from AT (HR: 1.26, p  = 0.380) and the addition of chemotherapy was associated with significantly worse OS compared to RT (HR: 1.76, p  = 0.046). Conclusion: In high‐risk patients, adjuvant chemoradiotherapy improved OS compared to RT alone. The greatest benefit was in node‐positive cases. In intermediate‐risk patients, the addition of chemotherapy to RT increased mortality risk and therefore should only be used cautiously in these patients. Abstract : The addition of chemotherapy to adjuvant radiotherapy could improve survival. This is observed only among high‐risk patients. When stratified by nodal status, the benefit exists only in node‐positive patients. In intermediate‐risk patients chemotherapy addition decreases survival. Risk categorization is important for treatment selection and survival outcomes.